Estrategias de arteterapia en la producción de textos creativos de personas jóvenes y adultas con escolaridad inconclusa, un caso de estudio en el Centro Educativo Comunitario Intercultural Bilingüe de Bachillerato PCEI "Yachay Ñan” - Zabala Jiménez, María de los Ángeles (2024)
This research aims to characterize the process of production of creative texts mediated by art therapy strategies of young people and adults with unfinished schooling in the Centro Educativo Comunitario Intercultural Bilingüe PCEI “Yachay Ñan." Using a qualitative approach and a case study methodology, the study delves into the phenomenon of creative writing in a specific group of people, in this case, individuals who dropped out of school and belong to a rural and bilingual environment. The art therapy techniques used, such as collage, automatic writing, and the creation of therapeutic letters, were the basis for encouraging writing. From the perspective of the participants, these techniques have contributed to the development of cognitive and creative skills by fostering the ability to express and materialize their own ideas. Observing the final products, it can be concluded that there was significant progress in the organization and textual concordance with the help of art therapy as a tool to promote writing skills.